Journalism education in Malaysia: dancing with UNESCO's model curricula - Ismail, Awan; Ismail, Rizalawati; Aripin, Norizah; Yusof, Norhafezah (International Organization Center of Academic Research (OCERINT), 2015)
Globally, journalism education is undergoing significant changes in lieu of the ongoing technological evolution. In recognition of the importance of journalism education and how it shapes journalism practices globally, in 2007 UNESCO has mapped out a framework for journalism education, especially for developing countries. This study seeks to identify the core values, knowledge, and skills needed in Malaysian journalism education and ascertain the degree to which they align with the model of journalism curriculum for developing countries proposed by UNESCO. To this end, the study conducted in-depth interviews with journalism scholars in Malaysian public universities and senior practitioners from media organisations. The results show the majority of educational components recommended by UNESCO are not compatible with journalism education in Malaysia.